Study of the prevalence and clinical manifestations of measles at present - Daria S. Kaskaeva; Elena A. Tepper; Marina M. Petrova (LLC "MEDIAFORMAT", 2024)
Today, the issue of measles is of great importance, since cases of this disease are currently increasingly common. Insufficient immunization coverage and the increase in the rate of measles vaccine refusal are considered to be the main cause of the incidence increase. Furthermore, it is important to note that an almost high rate of the atypical course of measles, specifically the emergence of the trend towards fusion of the rash, itching, no pigmentation period, no pathognomonic symptom (Belsky-Filatov-Koplik spots), the emergence of hepatomegaly, increased liver transaminases, and the development of diarrhea, is reported at the current stage. It is impossible to ignore the fact that measles can lead to severe complications, such as pneumonia, encephalitis, meningitis, hepatitis, etc. Measles can also be fatal, thereforore, it is necessary to understand the importance of prevention, timely treatment and diagnosis of this disease.